FUNCTIONAL-METHODICAL USE AND CHARACTERISTICS OF TOPONYM OPTIONS - Hamidova Kamola Mamirovna (Zeta Repository, 2023)
In the article, the content and essence of the functional-methodical use and characteristics of some toponym variants found in artistic speech are analyzed and scientifically based.